Práticas pedagógicas em classes multisseriadas: inserção da educação popular no currículo das escolas do campo - Costa, Luciélio Marinho da (2019)
The following paper presents a doctoral research on the pedagogical practices employed by rural multigrade schools and the use of Popular Education principles in the development of a curriculum guided by Rural Education concepts. We analyzed the pedagogical practices implemented by the Zumbi dos Palmares School situated in the Brazilian small town of Marí. Our theoretical and methodological frames of reference incorporated the principles of Rural Popular Education and their transformative process of the Pedagogical Political Project, resulting in an exceptional curricular organization for multigrade rural schools. Our specific goals are: to present the experiences of teachers undergoing post-graduation education while working at multigrade rural schools; to produce a methodological research method based on the aforementioned principles of Rural Popular Education, the Political-Pedagogical Project of the Zumbi dos Palmares School and its implementation through the pedagogical practices of its teachers; to elaborate a theoretical approach that encourages reflections on popular education guided by Paulo Freire's work on country social movements and education for multigrade rural schools; to understand the curricular and pedagogical organization of rural school's multigrade classes through examination of the aforementioned school; to argue that the Popular Education principles lead to an exceptional curricular organization for multigrade rural schools, according to the analysis of pedagogical practices employed by the Zumbi de Palmares School. Our theoretical frame of reference includes the concepts of pedagogical practices, multigrade rural school and popular education, among others. Our research methodology is based on qualitative research methods, focusing on case study. Data collection involved both document analysis and semi-structured interviews of six teachers from the school - including four in teaching positions, one manager and one supervisor. We concluded that Popular Education can be integrated to the pedagogical practices of multigrade rural schools through starting themes, thus reinforcing the rural identity of the settlement.